Gift eaudiobook A horse, a boy, and a miracle of love. - Snelling, Lauraine (Mission Audio, 2012)
Beloved, bestselling author Lauraine Snelling weaves a story of holiday romance, which begins with a simple advertisement for a horse's companion. Turner McNeally's daughter has gone off to college, and her horse is demonstrating signs of loneliness. Rebecca Wilkinson's son hasn't spoken a word since his father's death, and the family counselor suggests a pet. What will Christmas bring these troubled hearts? And what is this gift from God that Turner McNeally keeps talking about?